2022
DOI: 10.1177/21925682221120533
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Slope is a Predictor of Fusion Rate in Single Level Anterior Cervical Discectomy and Fusion

Abstract: Study design Retrospective study Objectives To explore preoperative segmental slope as a predictor of fusion rate after single-level anterior cervical discectomy and fusion (ACDF). Methods Data of consecutive patients with single-level cervical spondylosis who underwent ACDF between 2011 and January 2019 were retrospectively reviewed. Preoperative parameters including baseline characteristics, segment slope, T1 slope, range of motion, intervertebral disk height, and bone density were evaluated. Data were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Surgical level slope may be influenced by the T1 slope, which acts like the abutment of the cervical spine. Sheng et al ( 18 ) found an obvious correlation between T1 slope and surgical level slope. They also determined that increasing surgical level slope was a risk factor for non-fusion at postoperative early stage.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Surgical level slope may be influenced by the T1 slope, which acts like the abutment of the cervical spine. Sheng et al ( 18 ) found an obvious correlation between T1 slope and surgical level slope. They also determined that increasing surgical level slope was a risk factor for non-fusion at postoperative early stage.…”
Section: Discussionmentioning
confidence: 98%
“…Cervical sagittal alignment plays an important role in transmitting axial loads and maintaining biomechanical balance of the cervical spine, and might be related to the bone remodeling process after anterior cervical surgery ( 16 ). Studies have suggested that surgical segment slope may influence the intervertebral fusion process after ACDF ( 17 , 18 ). Cervical sagittal vertical axis (SVA) has also been reported to be associated with the anterior bone formation after CDR ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although a lack of fusion may be asymptomatic, it may potentially lead to complications 13,14 , even a reoperation. In addition, failure to achieve early fusion may result in prolonged neck-brace wear 15 , a delayed return to work, reduced patient satisfaction 16 , and a delayed return to play for athletes 17,18 .…”
mentioning
confidence: 99%